Robusta coffee transpiration rate in smallholder coffee plantations on Inceptisols of Malang, East Java - Jiyanti Yana Saputri; Sugeng Prijono; Budi Prasetya (Journal of Degraded and Mining Lands Management, 2021)
Climate change and the erratic and uneven rainfall distribution are the causes of reduced water available in the soil for plant needs to the transpiration process. This study aimed to determine coffee transpiration rate on dry land with rain harvesting techniques during the dry season, transition season, and rainy season and the factors that influence it. This study used field observation and laboratory analysis with two treatments, i.e. a bench terrace as a control (P1) and an L-shaped silt pit (P2). The variables observed were soil moisture content, transpiration rate, soil water potential, leaf water potential, and microclimate, especially temperature and sunlight intensity. The results showed that the transpiration rate of coffee plants was significantly different in the two treatments. The highest transpiration rate was found in P2 as much as 13.17 mm week-1 or equivalent to 1.88 mm day-1 during the dry season. Application of the L-shaped silt pit (P2) increased soil moisture content compared to the control (P1). This increase was followed by an increase in soil water potential and leaf water potential, which could reach the highest values of 0.18 bar and 0.49 bar, respectively. The transpiration decreases with the change of seasons from the dry season to the transitional season and the rainy season. This decrease is caused by changes in the microclimate, especially the temperature and sunlight intensity. Both are the most variables that affect the rate of transpiration.